Interaction patterns of methoprene-tolerant and germ cell-expressed Drosophila JH receptors suggest significant differences in their functioning - Kolonko-Adamska, M.; Zawadzka-Kazimierczuk, A.; Bartosińska-Marzec, P.; Koźmiński, W.; Popowicz, G.; Krężel, A.; Ożyhar, A.; Greb-Markiewicz, B. (Frontiers in Molecular Biosciences, 2023)
20E -20-hydroxyecdysone AF2 -activation function 2 bHLH-PAS -basic helix-loop-helix/Per-Arnt-Sim FISC -βFtz-F1-interacting steroid receptor coactivator Ftz-F1 -orphan nuclear receptor Fushi Tarazu factor-1 Gce -Germ cell-expressed GceC -Gce C-terminus IMAC -immobilized metal affinity chromatography ITC -isothermal titration calorimetry JH -juvenile hormone Kd -dissociation constant LBD -ligand binding domain Met -Methoprene tolerant MetC -Met C-terminus MoREs -transient motifs of the secondary structure NES -nuclear export signal NLS -nuclear localization signal NMR -nuclear magnetic resonance NR-box -nuclear receptor box PCR -polymerase chain reaction SRC -steroid receptor coactivator TAD -transactivation domain TAI -steroid-hormones coactivator Taiman TF -transcription factors